Calcium channels contribute to albiflorin-mediated antinociceptive effects in mouse model. (15th August 2016) - Zhang, Yizhi; Sun, Dejun; Meng, Qingjin; Guo, Wanxu; Chen, Qiuhui; Zhang, Ying
Highlights: AF shows strongly antinociceptive activity in mouse models. AF regulated nNOS and 5-HT levels in serum and hypothalamus of mouse. AF regulated the phosphorylation of CaMKII and JNK in hypothalamus of mouse. Ca 2+ channels are involved in AF-mediated antinociceptive activity. KATP channels may be involved in AF-mediated antinociceptive activity. Abstract: Albiflorin (AF), one of important bioactive constituents of Paeonia lactiflora Radix, possesses neuro-protective effect. The present study aims to investigate the antinociceptive activities of AF and possible mechanisms. AF suppressed acetic acid-caused writhing, lengthened the latency period of mouse in hot plate test, and reduced the licking and biting response time of the injected mouse paw during phase I and phase II, and it suggested that AF exerted the antinociceptive activity mainly through central nervous system. Nimodipine, a commonly used calcium channels blocker, strongly lengthened AF-enhanced latency period of mouse in hot plate test. Compared with control group, AF reduced the levels of euronal nitric oxide synthase (nNOS), and enhanced the levels of serotonin (5-HT) in serum and/or hypothalamus before and after 30-s thermal stimuli. The reduced activation of calmodulin-dependent protein kinase II and c-Jun N-terminal kinase in hypothalamus was observed in AF-treated mice. Collectively, AF-mediated antinociceptive activities were, at least partially, related to calcium channels.